2007
DOI: 10.1037/cjep2007007
|View full text |Cite
|
Sign up to set email alerts
|

Identification variability as a measure of loudness: An application to gender differences.

Abstract: It is well known that discrimination response variability increases with stimulus intensity, closely related to Weber's Law. It is also an axiom that sensation magnitude increases with stimulus intensity. Following earlier researchers such as Thurstone, Garner, and Durlach and Braida, we explored a new method of exploiting these relationships to estimate the power function exponent relating sound pressure level to loudness, using the accuracy with which listeners could identify the intensity of pure tones. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…Gender differences in adaptation will result in gender differences in n, with female n's exceeding those of males (Table 2), in accordance with previous research (Sagi et al, 2007). Eq.…”
Section: Tablesupporting
confidence: 84%
See 2 more Smart Citations
“…Gender differences in adaptation will result in gender differences in n, with female n's exceeding those of males (Table 2), in accordance with previous research (Sagi et al, 2007). Eq.…”
Section: Tablesupporting
confidence: 84%
“…However, males incur greater permanent noise-induced hearing loss (Royster et al, 1980). Using a toneidentification paradigm, Sagi et al (2007) report gender differences in the psychophysical parameter, n, found in Stevens' power law, L = ku n , relating the loudness of a tone, L, to the physical intensity of the tone, u. Male exponents are found to be about 25% smaller than those of females, indicating differences in loudness perception.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The exponent values for the lowest two frequencies, 125 Hz and 250 Hz, are lower than those obtained by analysis of equal loudness contours ("Fletcher-Munson" curves). The values for n at these frequencies are consistent with those reported by Sagi et al (2007).…”
Section: Calculating the Value Of The Loudness Exponent From Adaptatisupporting
confidence: 90%
“…Females also demonstrate more acute sound sensitivity than males (Rogers et al, 2003, Sagi et al, 2007). These differences are reduced during menopause (Hultcrantz et al, 2006, Murphy and Gates, 1997, Wharton and Church, 1990), in females taking oral contraception (McFadden, 2000), and in females who have a male twin (McFadden, 1993a, McFadden et al, 1996), which suggests a role of hormones, including estrogen, in improving auditory function in females (McFadden, Martin, 2009).…”
Section: Discussionmentioning
confidence: 99%